Preparation and characterization of iron(iii) complex of saccharin (Journal of Bangladesh Academy of Sciences, 2014)
Complex of iron(III) with saccharin, [Fe(C7H4O3SN)2Cl] has been prepared in aqueous medium. The IR and electronic spectral analysis suggest that two saccharin molecules are attached to the metal ion through N atom and there is no chemically coordinated or crystalline water in the complex molecule. The magnetic moment value indicates the paramagnetic character of the complex. The cyclic voltammetric study indicates a quasi-reversible electron transfer process due to the presence of iron in the compound. DOI: http://dx.doi.org/10.3329/jbas.v37i2.17560 Journal of Bangladesh Academy of Sciences, Vol. 37, No. 2, 195-203, 2013